Effect of Bhramari Pranayama and Om Chanting on Psychosomatic Health-A Conceptual Study - Patel, Namita; Sharma, Kamlesh Kumar (International Research Journal of Ayurveda & Yoga, 2022)
People’s lifestyles have become highly mechanical in today’s world. Everyone is in a rat race to meet their objectives, which causes stress. This stress has a negative impact on a person’s physical and mental health. Mental health refers to the healthy development of emotional attitudes and personalities that coexist with the rest of society or community. Alterations in thinking, emotion, or behaviour are associated with reduced functioning in mental disorders. Healthy nutrition, daily regimen, seasonal regimen, and exercise, among other things, are important preventative measures for physical health, whereas Sadvrittapalan, application of Acharrasayana, yoga, and meditation practises are important for mental and physical health prevention. Yoga consists of eight stages, one of which, Pranayam, is crucial for achieving control over the Indriyas, or sense organs. Bhramari Pranayam is an important sort of Ashtakumbhaka that is also quite simple to do. The vibrations produced by Bhramari Pranayam’s humming sound directly touch the hypothalamus of the brain, generating a resonance in the mind that reduces tension and brings tranquilly and happiness to the entire body. Yoga is both a science and a way of life that originated in India. Om is the word or emblem of God, and Pranayama is an aspect of yoga that enhances mental wellness. It is the syllable of the past, present, and future, and is made up of three letters: A, U, and M. Om is the source of all thoughts, and chanting or meditating about it will bring you into a calm state of mind. The present conceptual study to assess the effectiveness of Bhramari Pranayama and Om chanting on physical and mental health.